Processes of secondary concentration of potentially toxic elements by the hydrocarbons during their ontogenesis - S. P. Yakutseni (Известия высших учебных заведений: Геология и разведка, 2015)
Geochemical parameters of hydrocarbon pools with their further enrichment of the potentially toxic elements during ontogenesis are considered. The mechanisms of the metal accumulation by hydrocarbons are discussed, in particular, peculiarities of the metal sequestration by hard and soft acids and bases. The highest concentrations of V, Ni, Zn, Co, Au and other metals are expected in oil on the base of metal complexes. The most active enrichment of the oil by microcomponents, including potentially toxic elements, takes place on the protooil generation stage.